A Review on Metamaterial Absorbers: Microwave to Optical - Abdulkarim, Yadgar I.; Mohanty, Ayesha; Acharya, Om Prakash; Appasani, Bhargav; Khan, Mohammad S.; Mohapatra, S. K.; Muhammadsharif, Fahmi F.; Dong, Jian (Frontiers in Physics, 2022)
Metamaterials (MM) are artificially designed materials that possess unique properties due to their geometrical design. They also display some peculiar properties, such as negative refractive index, Snell's law reversal, Doppler effect reverse, and left-handed behavior. MMs are used in a myriad of applications, including invisibility cloaking, perfect lensing, perfect absorption, and sensing. In this review article, the property of electromagnetic absorption by structures known as metamaterial absorbers (MMAs) is discussed. An MMA is a composite made up of many layers of metallic patterns separated by dielectric. This novel device helps in achieving near-unity absorption by various mechanisms, which are investigated in this article. The MMAs are classified based on their absorption characteristics, such as polarization tunability, broadband operation, and multiband absorption, in different frequency regimes.